1996
DOI: 10.1007/s004330050013
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of latex and silicone T tubes in the porcine common bile duct: an experimental study

Abstract: Toxicity of materials used in indwelling drains or catheters has the potential to damage surrounding tissues. The biocompatibility of biliary T-tubes was investigated using in groups of piglets (total 30 animals). In group 1 (n=16) a choledochotomy was performed with insertion of a latex T-tube (n=6) or a silicone T-tube (n=8), or without a T-tube (n=2). In group 2 (n=14) the common bile duct (CBD) was 3/4-transected, and the lesion was sutured over a latex T-tube (n=4) or a silicone T-tube (n=5), or without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…19 For stenting of the biliary duct, it has previously been shown that latex has desirable properties such as rapid tissue tract formation. 20,21 We have not examined physical and mechanical material properties (i.e., hardness, elasticity, and surface quality) of these tubes, even though it might have a stronger impact on the regenerating epithelium than the substance per se.…”
mentioning
confidence: 99%
“…19 For stenting of the biliary duct, it has previously been shown that latex has desirable properties such as rapid tissue tract formation. 20,21 We have not examined physical and mechanical material properties (i.e., hardness, elasticity, and surface quality) of these tubes, even though it might have a stronger impact on the regenerating epithelium than the substance per se.…”
mentioning
confidence: 99%
“…Therefore, it is likely that FBR to ST, a material with low biological reactivity, 19 proceeds to form TSS composed of two layers regardless of the genomic‐ or immune‐related backgrounds of mice. When the same experiment was conducted with both silicone and latex, there was a noticeable difference in the course of the experiment 20 . Future studies are needed to verify the relationship between FBRs and other materials and their immunological status.…”
Section: Discussionmentioning
confidence: 99%
“…When the same experiment was conducted with both silicone and latex, there was a noticeable difference in the course of the experiment. 20 Future studies are needed to verify the relationship between FBRs and other materials and their immunological status.…”
Section: Discussionmentioning
confidence: 99%
“…Koivusalo et al found that latex tubes were toxic and induced moderate to pronounced fibrosis and epithelial damage on the CBD wall, unlike silicone tubes. 5 There are various indications for biliary stenting like CBD stone, CBD stricture, biliary leak, peri ampullary carcinoma, CBD malignancy, etc. 6 The mean duration of the patency of the stent was about 12 months, but if not removed within (4-6 weeks), stent can act as nidus for stone formation.…”
Section: Figure 3 Cbd Stent With Encircling Stonementioning
confidence: 99%